1997
DOI: 10.1103/physrevlett.79.4778
|View full text |Cite
|
Sign up to set email alerts
|

Giant Intermolecular Decay and Fragmentation of Clusters

Abstract: In sharp contrast to molecules, electronic states of clusters with an excited intermediate-shell electron can efficiently decay via an intermolecular Coulombic mechanism. Explicit examples are presented using large scale ab initio propagator calculations. The mechanism is illustrated and its generality is stressed. [S0031-9007(97) PACS numbers: 36.40.Cg, 31.50. + w, 34.50.Gb Quantum states of electronic systems typically decay by photon and/or electron emission. Energetically low lying states decay radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
627
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 685 publications
(639 citation statements)
references
References 24 publications
11
627
0
1
Order By: Relevance
“…[10][11] In recent years a set of novel non-local autoionization processes has been identified to play an important role in weakly bonded atomic and molecular systems. [12][13][14] One such relaxation process is Intermolecular Coulombic Decay (ICD), initially observed upon innervalence ionization of van der Waals-bonded clusters, 12,[15][16][17] and later also (hydrogen bonded) water clusters. 18 In the ICD process, the energy provided by an outer valence electron upon filling the vacancy is used to expel a second electron from an atom or molecule neighboring the initially ionized site.…”
Section: Identifying the Initial Products Of The Interaction Of High-mentioning
confidence: 99%
“…[10][11] In recent years a set of novel non-local autoionization processes has been identified to play an important role in weakly bonded atomic and molecular systems. [12][13][14] One such relaxation process is Intermolecular Coulombic Decay (ICD), initially observed upon innervalence ionization of van der Waals-bonded clusters, 12,[15][16][17] and later also (hydrogen bonded) water clusters. 18 In the ICD process, the energy provided by an outer valence electron upon filling the vacancy is used to expel a second electron from an atom or molecule neighboring the initially ionized site.…”
Section: Identifying the Initial Products Of The Interaction Of High-mentioning
confidence: 99%
“…Atomic and molecular phases comprise mainly localized electronic orbitals, and the decay rate is consequently quite small for processes involving electron emission from any atomic site other than that originally excited. In such systems, this type of ''off-site'' emission has been labeled as ICD, inter-Coulombic (atomic or molecular) decay [3].Although ICD has been studied primarily in the context of valence excitations [3][4][5], recent experiments have shown that core-excited systems may also decay in this fashion, as shown schematically in Fig. 1 [6].…”
mentioning
confidence: 99%
“…In contrast, in weakly bound complexes, locally generated electrons can additionally interact with neighboring atoms or molecules, leading to new interatomic or intermolecular interactions. Interatomic Coulombic decay (ICD) is a particularly interesting decay process which occurs when local electronic decay is energetically forbidden [1]. Thus, ICD offers a new, ultrafast decay path where energy is exchanged with a neighboring atom leading to its ionization.…”
mentioning
confidence: 99%